Resin composition for injection molding, injection molded article, method for manufacturing injection molded article, and method for analyzing injection molded article

The resin composition with non-fibrous inorganic particles and controlled aggregates addresses the issue of anisotropy in injection molded products, enabling precise resin orientation estimation and improved dimensional accuracy.

JP7608392B2Active Publication Date: 2025-01-06FURUKAWA ELECTRIC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2022090031
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-06-02
Publication Date
2025-01-06
Estimated Expiration
2042-06-02

Smart Images

  • Figure 0007608392000002
    Figure 0007608392000002
  • Figure 0007608392000003
    Figure 0007608392000003
  • Figure 0007608392000004
    Figure 0007608392000004
Patent Text Reader

Abstract

To estimate orientation of a resin while suppressing anisotropy.SOLUTION: A resin composition for injection molding of the present invention is an injection-molded article including a first thermoplastic resin and a filler including a non-fibrous first inorganic particle, and further includes at least one of an aggregate of a second inorganic particle or a resin composition of a second thermoplastic resin. In lengths of the aggregate and the resin composition in three directions orthogonal to each other, a ratio of a first length which is the longest and a second length which is the shortest is 2 or more and 20 or less, the first length is 25 μm or more and 100 μm or less, and the first inorganic particle having a particle diameter of 25 μm or more is not included in the aggregate or the inside of the resin composition.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition for injection molding, an injection molded article, a method for producing an injection molded article, and a method for analyzing an injection molded article. [Background technology]

[0002] There is a known technique for analyzing the thermal expansion and contraction direction of an injection molded product by using the filler in the injection molded product as a tracer. The technique described in Patent Document 1 estimates the flow direction of the resin from the fiber direction of the fibrous inorganic particles in the injection molded product, and analyzes the hot warpage of the injection molding. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2014-100879 A Summary of the Invention [Problem to be solved by the invention]

[0004] Since the fibrous inorganic particles cannot deform in accordance with the expansion and contraction of the surrounding resin, they restrict the deformation of the resin, thereby increasing the anisotropy of the injection-molded product.

[0005] The present invention has been made in consideration of the above problems, and has an object to make it possible to estimate the orientation of a resin while suppressing anisotropy. [Means for solving the problem]

[0006] According to one aspect of the present invention, there is provided a resin composition for injection molding comprising a first thermoplastic resin and a filler containing non-fibrous first inorganic particles, further comprising at least one of an aggregate of second inorganic particles or a resin composition of a second thermoplastic resin, wherein, in the lengths of the aggregate and the resin composition in three mutually perpendicular directions, the ratio of the longest first length to the shortest second length is 2 or more and 20 or less, the first length is 25 μm or more and 100 μm or less, and the first inorganic particles having a particle size of 25 μm or more are not contained inside the aggregate or the resin composition.

[0007] According to another aspect of the present invention, there is provided a method for producing an injection-molded product, comprising a first step of kneading a first thermoplastic resin, non-fibrous first inorganic particles, and at least one of an aggregate of second inorganic particles or a resin composition of a second thermoplastic resin, and a second step of injection molding the mixture from the first step, wherein, in lengths of the aggregate and the resin composition in three mutually perpendicular directions, the ratio of the longest first length to the shortest second length is 2 or more and 20 or less, the first length is 25 μm or more and 100 μm or less, and no first inorganic particles having a particle size of 25 μm or more are contained inside the aggregate or the resin composition.

[0008] According to another aspect of the present invention, there is provided a method for analyzing an injection-molded product, comprising the steps of: acquiring a tomographic image of an injection-molded product comprising a first thermoplastic resin, non-fibrous first inorganic particles, and at least one of an aggregate of second inorganic particles or a resin composition of a second thermoplastic resin; and determining the orientation of the aggregate or the resin composition in the tomographic image, wherein, in the lengths of the aggregate and the resin composition in three mutually perpendicular directions, the ratio of the longest first length to the shortest second length is 2 or more and 20 or less, the first length is 25 μm or more and 100 μm or less, and no first inorganic particles having a particle size of 25 μm or more are contained within the aggregate or the resin composition. Effect of the Invention

[0009] According to the present invention, it is possible to estimate the orientation of a resin while suppressing anisotropy. [Brief description of the drawings]

[0010] [Figure 1] FIG. 2 is an external view of a ferrule according to an embodiment of the present invention. [Diagram 2] 4 is a flowchart illustrating a method for manufacturing a ferrule according to one embodiment of the present invention. [Diagram 3] FIG. 2 is a cross-sectional view of a ferrule according to one embodiment of the present invention. [Figure 4] FIG. 2 is a cross-sectional view of a ferrule according to one embodiment of the present invention. [Diagram 5] FIG. 1 is a schematic diagram of a resin orientation analysis device according to an embodiment of the present invention. [Figure 6] 1 is a flowchart of a method for analyzing resin orientation according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The injection molding resin composition and injection molded article according to the embodiment of the present invention will be described using a ferrule used in an optical fiber connector as an example.

[0012] Fig. 1 is an external view of a ferrule according to this embodiment. The ferrule (part for optoelectronic devices) is used as an optical connector for optically connecting optical fibers. Fig. 1 shows a ferrule for an MT (Mechanically Transferable) connector, but the ferrule in this embodiment may be an MPO (Multifiber Push-On) connector or the like.

[0013] 1, the ferrule 10 is substantially rectangular, and a plurality of optical fiber insertion holes 12 are formed in an end face 18 of the ferrule 10. The optical fiber core 14 includes a plurality of optical fibers 16, and the optical fibers 16 are inserted into each of the optical fiber insertion holes 12 and fixed by an adhesive or the like. The end face 18 is polished by, for example, PC (Physical Contact) polishing, SPC (Super PC) polishing, UPC (Ultra PC) polishing, APC (Angled PC) polishing, or the like.

[0014] It is not necessary that a plurality of optical fiber insertion holes 12 are formed in the ferrule 10. When the optical fiber core 14 is a single-core core including only a single optical fiber 16, the ferrule 10 has a single optical fiber insertion hole 12 formed therein.

[0015] The ferrule 10 is further formed with a pair of guide pin insertion holes 20. The pair of guide pin insertion holes 20 are formed in the ferrule 10 so as to be located on both sides of the multiple optical fiber insertion holes 12. The pair of guide pin insertion holes 20 are each formed in the ferrule 10 along the connection direction of the optical fiber 16. A guide pin 22 for alignment is inserted into the pair of guide pin insertion holes 20, respectively.

[0016] A guide pin 22 is inserted into each guide pin insertion hole 20 of the pair of ferrules 10, and the two ferrules 10 are aligned. The two end faces of the optical fiber 16 come into contact with each other, and the two ferrules 10 are fixed by a fixing jig such as a clip. This connects the optical fiber 16. Note that the configuration for aligning and fixing the two ferrules 10 is not limited to this. The two ferrules 10 may be aligned and fixed via an adapter, for example.

[0017] Next, the injection molding resin composition used for the ferrule will be described. The injection molding resin composition is injected into a mold to produce a ferrule 10 as an injection molded product. The injection molding resin composition in this embodiment contains a first thermoplastic resin and first inorganic particles (non-fibrous inorganic particles) as a filler. The injection molding resin composition further contains at least one of an aggregate of second inorganic particles or a resin composition of a second thermoplastic resin as a tracer. The components of the injection molding resin composition will be described in detail below.

[0018] [First thermoplastic resin] The first thermoplastic resin is a matrix resin constituting the continuous phase of the ferrule 10. The first thermoplastic resin is a resin with excellent precision moldability, and is suitable as a matrix resin constituting the continuous phase of the ferrule 10 that requires precision molding. The first thermoplastic resin is not particularly limited, but includes polyphenylene sulfide (PPS) resin, polycarbonate (PC) resin, polyethersulfone (PES) resin, liquid crystal polymer (LCP), modified polyphenylene ether (PPE), polyetheretherketone (PEEK) resin, etc., and is preferably PPS resin from the viewpoints of dimensional stability, strength, moldability, etc. The PPS resin may have a crosslinked or linear structure, and its structure, molecular weight, etc. can be appropriately selected and used according to the properties required for the ferrule 10.

[0019] The first thermoplastic resin is not limited to one type of resin, and may be composed of multiple types of resin. Furthermore, the first thermoplastic resin may be a mixture of multiple different grades of resin of the same type. For example, the first thermoplastic resin may be one type of PPS resin, a mixture of two grades of PPS resin, a crosslinked type and a linear type, or a mixture of PPS resin and an elastomer resin.

[0020] The first thermoplastic resin, like the aggregate and the resin composition, may be colored black with carbon black, etc. The coloring of each component will be described later.

[0021] [aggregate] The aggregates are composed of inorganic particles such as silica particles, calcium carbonate, and carbon black, and are used as tracers. When inorganic particles of carbon black such as furnace black, acetylene black, and thermal black are used, it becomes possible to easily control the size of the aggregates. In particular, furnace black has high stability as an aggregate, and is therefore suitable as an inorganic particle that constitutes the aggregates.

[0022] The aggregate preferably has an anisotropic shape such as a rod shape or a flat shape so that it can function as a tracer. In the aggregate, the aspect ratio of the longest first length and the shortest second length among the lengths in three mutually perpendicular directions can preferably be 2 or more and 20 or less. For example, when the aggregate is flat, the first length corresponds to the long axis of the aggregate in a plan view, and the second length corresponds to the short axis of the aggregate and the thickness perpendicular to the long axis. The aggregate is oriented according to the flow direction of the resin in the injection molding process, and the longitudinal direction (first direction) of the aggregate faces the flow direction of the resin. In addition, the main surface of the flat aggregate is parallel to the flow direction of the resin. In this way, the aggregate has a relatively large aspect ratio, so that the aggregate can function as a tracer for estimating the flow direction of the resin during injection molding.

[0023] If the major axis of the aggregate is too short, the aggregate cannot be clearly observed using a general optical microscope or digital microscope. On the other hand, if the major axis of the aggregate is too long, the aggregate becomes visible to the naked eye on the surface of the ferrule 10, which may impair the aesthetic appearance of the product. Furthermore, the aggregate may be easily divided during the manufacturing process of the ferrule 10. For these reasons, the major axis of the aggregate is preferably 25 μm or more and 100 μm or less.

[0024] The aspect ratio and major axis of the aggregate can be appropriately adjusted to desired values ​​depending on conditions such as the particle size of the inorganic particles, the presence or absence of granulation treatment, the screw rotation speed and kneading temperature during injection molding, etc. Furthermore, when carbon black is used as the aggregate, the aspect ratio and major axis of the aggregate can be adjusted to desired values ​​depending on the oil absorption of the carbon black.

[0025] The particle size of the inorganic particles constituting the aggregate is preferably 1 μm or less. Carbon black is an aggregate composed of carbon particles of 1 μm or less, and is suitable as the inorganic particles constituting the aggregate. If the particle size of the inorganic particles exceeds 1 μm, the inorganic particles constituting the aggregate may restrain the movement of the surrounding resin, hindering the expansion and contraction of the surrounding resin, and increasing the anisotropy.

[0026] As inorganic particles constituting the aggregate, particles with strong cohesiveness, with large van der Waals forces acting between inorganic particles, are preferred. For example, the Hamaker constant of inorganic particles in a vacuum may be 10 or more. Graphite and silica particles are preferred because they have high cohesiveness, and carbon black is particularly preferred because it has high cohesiveness. Due to the strong cohesiveness of inorganic particles, the aggregates are difficult to break down to a size that cannot be visually recognized during the process, and the aggregates can function as tracers in the molded product.

[0027] An aggregate made of inorganic particles with a small particle size can be slightly deformed by tensile stress or compressive stress from the resin surrounding the aggregate, regardless of the shape of the inorganic particles. Therefore, compared with a single inorganic particle, an aggregate of inorganic particles does not restrict the movement of the surrounding resin, and can reduce thermal deformation and anisotropy in an injection molded product. A plurality of inorganic particles are aggregated by attractive forces between surfaces such as Coulomb force and van der Waals force. Here, when a force is applied to the inorganic particles from the surrounding resin, each of the inorganic particles can move relatively a short distance while maintaining surface contact. Therefore, in the injection molding process, the aggregate is oriented according to the flow of the surrounding resin without being separated into individual inorganic particles. The aggregate can maintain its shape, such as a flat or rod-like shape, until the final product and function as a tracer. In this way, by using an aggregate of inorganic particles as a tracer, it is possible to achieve an effect that cannot be achieved by a single inorganic particle, that is, not to hinder the expansion and contraction of the surrounding resin. In addition, the aggregate can expand or contract with the temperature change of the surrounding resin, but the shape of the aggregate does not change significantly. In addition, in the injection molding process, shear stress is applied to the aggregate, and the aggregate may be slightly elongated in the direction of the shear stress. However, even in this case, the shape of the aggregate does not change significantly, and the function as a tracer is not lost.

[0028] [Resin composition] The resin composition is composed mainly of a second thermoplastic resin. The resin composition may have the same aspect ratio and size as the aggregate described above. That is, the resin composition preferably has an aspect ratio of 2 to 20 and a major axis of 25 μm to 100 μm. This makes the resin composition easier to identify as a tracer. As an example, the resin composition may be resin burn that occurs when a resin is excessively heated.

[0029] The second thermoplastic resin constituting the resin composition may preferably be a polyarylene sulfide such as PPS resin. When the polyarylene sulfide is heated, molecular crosslinking and extension occur, and the molecular weight increases. In addition, the softening point increases and the polyarylene sulfide becomes insoluble, accompanied by blackening. Therefore, the polyarylene sulfide that has turned black by heating no longer melts even at the molding temperature while maintaining its strength and elasticity, and can function as a tracer. The resin composition has a higher softening temperature than polyarylene sulfide. In addition, since the resin composition is mainly composed of polyarylene sulfide, it has a specific gravity similar to that of polyarylene sulfide.

[0030] The resin composition may be molded to a desired aspect ratio and size in advance, and then added to a resin composition for injection molding such as a first thermoplastic resin. Alternatively, instead of adding a resin composition consisting of a second thermoplastic resin, a resin composition in which a part of the first thermoplastic resin has turned black may be used as a tracer. That is, when a mixture containing the first thermoplastic resin is extruded by the heated screw of a twin-screw kneading extruder, a resin burn (resin composition) in which a part of the first thermoplastic resin has turned black is generated. For example, by setting the screw temperature of the twin-screw kneading extruder to 330°C or higher, the thermoplastic resin is baked onto the screw surface. Furthermore, by appropriately adjusting the screw rotation speed, the resin composition may have a desired aspect ratio and size.

[0031] It is preferable that the resin composition is not melted or divided by heating during the injection molding process. That is, it is preferable that the softening temperature of the resin composition is higher than that of the first thermoplastic resin. As a result, the resin composition is not melted or divided during the injection molding process, and the resin composition can maintain the function of a tracer. The softening temperature of the resin composition can be measured using a scanning probe microscope (SPM). Specifically, the resin composition is heated while the probe of the SPM is pressed against the resin composition. The softening temperature of the resin composition is measured by reading the displacement of the resin composition at this time. The softening temperature of the crystalline resin is a temperature near the melting point, and the softening temperature of the non-crystalline resin is a temperature near the glass transition point. For example, the first thermoplastic resin can be a PPS resin (melting point about 290°C), and the second thermoplastic resin contained in the resin composition can be a PEEK resin (melting point 334°C).

[0032] The second thermoplastic resin constituting the resin composition is not limited in type as long as it expands and contracts without restraining the surrounding resins, but it is preferable that the second thermoplastic resin has the same characteristics as the first thermoplastic resin. In particular, when the second thermoplastic resin is the same type as the first thermoplastic resin, the specific gravity of the resin composition and the surrounding resins are approximately the same, and the affinity between the resin composition and the surrounding resins is improved. Therefore, it is possible to reduce separation between the resin composition and the surrounding resins and uneven distribution of the resin composition.

[0033] Even when the first thermoplastic resin and the second thermoplastic resin are the same type, the resin composition needs to be identified as a tracer. That is, the resin composition observed by a microscope or an X-ray CT device needs to have a color or brightness different from that of the surrounding first thermoplastic resin. For example, when the first thermoplastic resin and the second thermoplastic resin are both PPS, the resin composition can be identified as a tracer by turning black by heat treatment. The resin composition may also be colored with a pigment such as carbon black. In addition, when the first thermoplastic resin is also colored black with carbon black, it is preferable that the resin composition is colored blacker than the black of the first thermoplastic resin. As described above, the resin composition can be identified as a tracer by having a brightness lower than that of the first thermoplastic resin, i.e., the surrounding resins.

[0034] The tracer content of the resin composition or aggregate is not particularly limited, but can be appropriately determined according to various conditions such as the strength and appearance of the molded article, and the number of orientation information. When the tracer content in the molded article is small, the influence of the tracer on the strength and appearance of the molded article can be reduced. For example, when the tracer content is small and one tracer is contained for 10 molded articles, 100 tracers can be contained in 1000 molded articles manufactured under the same conditions. By observing 100 tracers, the orientation of the resin or molecules at 100 locations can be estimated, and sufficient orientation information can be obtained. In addition, when 1000 tracers are contained in one molded article, detailed orientation information can be obtained by observing a smaller number of molded articles. Even in this case, the volume per tracer is minute, so that the influence on the mechanical strength of the molded article is small enough to not cause a practical problem. Therefore, it is preferable that about 0.1 to 1000 tracers are contained in one molded article, and in this case, it is possible to obtain sufficient orientation information while minimizing the influence on the molded article.

[0035] [Non-fibrous inorganic particles] The non-fibrous inorganic particles (first inorganic particles) are used as a filler and constitute a dispersed phase in the continuous phase of the first thermoplastic resin. The inclusion of the filler in the first thermoplastic resin reduces the molding shrinkage rate of the ferrule 10, reduces the linear expansion coefficient, and improves the dimensional accuracy. The non-fibrous inorganic particles may be, for example, amorphous silica particles produced by crushing, calcium carbonate, etc.

[0036] The non-fibrous inorganic particles preferably have a shape and particle size that are distinguishable from the tracer aggregates and the resin composition. The shape and particle size of the non-fibrous inorganic particles are described in detail below.

[0037] It is preferable that the non-fibrous inorganic particles do not have a particle size of 25 μm or more inside the aggregate or resin composition. If non-fibrous inorganic particles having a large particle size are contained inside the aggregate and resin composition that are tracers, the visibility of the tracer may decrease. Therefore, by not containing non-fibrous inorganic particles having a particle size of 25 μm or more inside the aggregate or resin composition, it is possible to prevent the visibility of the tracer from decreasing.

[0038] The shape of the non-fibrous inorganic particles is preferably a symmetrical spherical or polygonal shape. In particular, when the non-fibrous inorganic particles are spherical, it is also possible to reduce the wear of the mold. Furthermore, the aspect ratio of the non-fibrous inorganic particles is preferably smaller than the aspect ratio of the aggregate and the resin composition. For example, when the aspect ratio of the aggregate and the resin composition is 2 or more, the aspect ratio of the non-fibrous inorganic particles is preferably 2 or less.

[0039] The particle diameter of the non-fibrous inorganic particles is preferably smaller than that of the aggregates and the resin composition. For example, when the major axis of the aggregates and the resin composition is 25 μm or more and 100 μm or less, the cumulative 99% particle diameter D 99 is preferably 25 μm or less, more preferably 10 μm or less. Here, the cumulative 99% particle diameter D 99is the particle size at which the cumulative small particle size is 99% in the cumulative particle size distribution curve based on volume. In other words, if almost all of the non-fibrous inorganic particles are 25 μm, it is possible to prevent the non-fibrous inorganic particles from being confused with the tracer aggregates and resin composition.

[0040] The lower limit of the particle size of the non-fibrous inorganic particles is not particularly limited. However, non-fibrous inorganic particles with a small particle size may increase the viscosity of the resin and cause a decrease in the terminal transferability of injection molding. For this reason, the cumulative 10% particle size D 10 In other words, the cumulative 10% particle diameter D of the non-fibrous inorganic particles is preferably 0.5 μm or more. 10 When the thickness is 0.5 μm or more, good fluidity of the resin can be maintained, and the occurrence of the above-mentioned defects can be prevented.

[0041] The amount of non-fibrous inorganic particles added in the resin composition for injection molding is preferably 50% by weight or more and 85% by weight or less, and more preferably 65% ​​by weight or more and 80% by weight or less. In the resin composition for injection molding, the first thermoplastic resin as the continuous phase and the non-fibrous inorganic particles as the dispersed phase form a so-called sea-island structure, and the non-fibrous inorganic particles have a clear outline between the surrounding first thermoplastic resin. Therefore, the non-fibrous inorganic particles are easily identified by optical microscopes, digital microscopes, X-ray CT, etc. In addition, the non-fibrous inorganic particles are easier to distinguish from the tracer in appearance, such as the color tone of the non-fibrous inorganic particles, compared to the first thermoplastic resin. Therefore, by making the amount of non-fibrous inorganic particles 50% by weight or more, the layer of the continuous first thermoplastic resin becomes smaller, making it easier to identify the tracer. Furthermore, when the amount of non-fibrous inorganic particles added is 65% by weight or more, it becomes even easier to identify the tracer. On the other hand, if the amount of non-fibrous inorganic particles added exceeds 85% by weight, the fluidity of the resin composition for injection molding decreases, making injection molding difficult. Therefore, it is preferable that the amount of non-fibrous inorganic particles added is 80% by weight or less. In this case, it is possible to maintain good fluidity of the resin and reduce defects such as insufficient filling at the end of the mold.

[0042] [Coloring] As described above, the resin composition for injection molding in this embodiment includes the first thermoplastic resin and the non-fibrous inorganic particles as a filler, and may further include an aggregate and a resin composition as a tracer. From the viewpoint of identifying the tracer and the appearance of the molded product, each element constituting the resin composition for injection molding may be colored as follows.

[0043] The first thermoplastic resin, the aggregate, and the resin composition are preferably the same color, and particularly preferably black. This makes the aggregate and the resin composition exposed on the surface of the ferrule 10 less noticeable, and the impact on aesthetics can be reduced. When the first thermoplastic resin, the aggregate, and the resin composition are black, the impact on aesthetics can be further reduced. The aggregate and the resin composition as tracers can be confirmed by magnified observation using a microscope or X-ray CT, and the shape and orientation of the tracer can be identified. In addition, the brightness of the aggregate and the resin composition is preferably lower than that of the colored first thermoplastic resin. In this case, it is possible to achieve both the aesthetics of the molded product surface and the visibility of the tracer.

[0044] As described above, since it is relatively easy to control the carbon black aggregates, the second inorganic particles constituting the aggregates are preferably carbon black. Furthermore, by adding the same type of carbon black to the first thermoplastic resin and coloring the first thermoplastic resin black, the deterioration of the aesthetic appearance due to the exposure of the aggregates can be further reduced. The brightness of the first thermoplastic resin can be appropriately adjusted according to the amount of carbon black added to the first thermoplastic resin. By making the brightness of the first thermoplastic resin higher than the brightness of the aggregates, that is, by making the blackness of the first thermoplastic resin lower than the blackness of the aggregates, the observation of the aggregates using a microscope becomes easy.

[0045] Even if the difference in brightness between the resin composition and the surrounding resin in visible light is not clearly visible by a microscope, the difference in the components of the two can be identified by an X-ray CT scanner. The tracer resin composition contains resin burnt that is the second thermoplastic resin oxidized at high temperature, so the oxygen content of the resin composition is higher than that of the surrounding resin. The difference in oxygen content can be shown on an X-ray image as a difference in X-ray absorption rate. Therefore, even if it is difficult to distinguish optically, it is possible to distinguish the tracer resin composition by using an X-ray CT scanner.

[0046] [Manufacturing method] Next, a method for producing a ferrule using the above-mentioned resin composition for injection molding will be described below. Fig. 2 is a flow chart showing the method for producing the ferrule 10 according to this embodiment.

[0047] In step S101, first, the tracer aggregate and resin composition are added to the first thermoplastic resin and non-fibrous inorganic particles. Here, the aggregate and resin composition can be molded to a predetermined aspect ratio and size in advance. The first thermoplastic resin, non-fibrous inorganic particles, aggregate and resin composition are stirred by a Henschel mixer or the like, and further kneaded by a twin-screw kneading extruder or the like. In this way, an injection molding resin composition containing a tracer is produced. Note that instead of adding a resin composition, a resin composition in which a part of the first thermoplastic resin has turned black may be used as a tracer. That is, when a mixture containing the first thermoplastic resin is extruded by the heated screw of the twin-screw kneading extruder, a resin burn (resin composition) in which a part of the first thermoplastic resin has turned black is produced. For example, by setting the screw temperature of the twin-screw kneading extruder to 330°C or higher, the thermoplastic resin is baked onto the screw surface. Furthermore, by appropriately adjusting the screw rotation speed, the resin composition can have a desired aspect ratio and size. When the resin composition is turned black by heat treatment, the outline of the resin composition may take on a brownish color, but the brown outline does not pose a problem in terms of the appearance of the molded product or the visibility of the tracer.

[0048] In step S102, the heated resin composition for injection molding is injected into a mold. After the resin for injection molding cools, the ferrule 10 is removed from the mold. Thereafter, as described below, by observing the tracer in the ferrule 10, it becomes possible to estimate the resin orientation.

[0049] [Cross-sectional image] Fig. 3 is a cross-sectional view of the ferrule 10 according to this embodiment. With the end face 18 of the ferrule 10 defined as the XY plane, the direction perpendicular to the XY plane is defined as the Z direction, and the position of the end face 18 of the ferrule 10 is defined as Z=0. By polishing the ferrule 10 in the Z direction from the end face, a cross section of the ferrule 10 appears. Fig. 3 shows a cross section of the ferrule 10 at Z=200 μm. At the position indicated by region A on the cross section, an inhomogeneous portion different from the surrounding resin, i.e., a tracer, is exposed.

[0050] FIG. 4 is an enlarged cross-sectional view of region A in the cross-sectional view of FIG. 3. FIG. 4(a) to FIG. 4(f) show enlarged cross-sectional views obtained by polishing the end face of the ferrule 10 in the Z direction by a predetermined length (10 μm). FIG. 4(a) shows a cross-section of the ferrule 10 at Z=190 μm. In FIG. 4(a), the tracer is not exposed on the cross-section. FIG. 4(b) shows a cross-section of the ferrule 10 at Z=200 μm. In FIG. 4(b), the length of the tracer in the X direction is 5 μm and the length in the Y direction is 15 μm. FIG. 4(c) shows a cross-section of the ferrule 10 at Z=210 μm. In FIG. 4(c), the length of the tracer in the X direction is 5 μm and the length in the Y direction is 30 μm. FIG. 4(d) shows a cross-section of the ferrule 10 at Z=220 μm. In FIG. 4(d), the length of the tracer in the X direction is 4 μm and the length in the Y direction is 60 μm. FIG. 4(e) shows a cross section of the ferrule 10 at Z=230 μm. In FIG. 4(e), the length of the tracer in the X direction is 3 μm and the length in the Y direction is 40 μm. FIG. 4(f) shows a cross section of the ferrule 10 at Y=240 μm. In FIG. 4(f), the tracer is not exposed on the cross section.

[0051] The tracer was observed at Z=200 μm, 210 μm, 220 μm, and 230 μm, so the length of the tracer in the Z direction is about 30 μm. The length of the tracer in the X direction is 5 μm, and the length in the Y direction is 60 μm. Therefore, the aspect ratio of the tracer was observed to be 60 / 5=12. This aspect ratio meets the above-mentioned conditions of this embodiment. By using the tracer in this embodiment, it is possible to estimate the orientation of the resin without increasing the anisotropy of the surrounding resin.

[0052] [Analysis equipment and method] 5 is a schematic diagram of a resin orientation analysis device in this embodiment. The analysis device 100 includes a table 101, a support 111, an X-ray irradiation unit 112, a support 121, an X-ray detection unit 122, an image processing unit 123, a first driving unit 131, a second driving unit 132, and a holder 133.

[0053] Table 101 is in the form of a long plate, placed on a ground surface (XY plane), and made of a hard material such as metal or glass. A columnar support 111 is provided on the upper left surface of table 101. Support 111 is columnar, and an X-ray irradiation unit 112 is provided on the upper portion of support 111.

[0054] A columnar support 121 is provided on the upper right surface of the table 101, and an X-ray detection unit 122 is provided on the upper part of the support 121. The X-ray detection unit 122 converts the X-rays that have passed through the ferrule 10 into an electrical signal and outputs a tomographic image to an image processing unit 123. The image processing unit 123 includes a processor, a memory, a display, etc., and can analyze the orientation of the resin in the ferrule 10 based on the tomographic image from the X-ray detection unit 122.

[0055] A first drive unit 131 including a motor, a rail, etc. is provided on the central upper surface of the table 101. A second drive unit 132 is provided on the upper surface of the first drive unit 131, and the first drive unit 131 can move the second drive unit 132 back and forth (X direction). The second drive unit 132 includes a motor, a rotating shaft that can be raised and lowered, etc., and a holder 133 is provided on the upper part of the second drive unit 132. The second drive unit 132 raises and lowers and rotates the rotating shaft, thereby enabling the holder 133 to move up and down and rotate. The holder 108 is flat, and the ferrule 10 is held by the holder 133.

[0056] The holder 133 moves and rotates while holding the ferrule 10, so that the X-ray irradiation unit 112 can irradiate the ferrule 10 with X-rays at various positions and in various directions. This allows the X-ray detection unit 122 to obtain a tomographic image of an arbitrary cross section of the ferrule 10, and the image processing unit 123 to analyze the resin orientation based on the image of the tracer contained in the tomographic image.

[0057] The resin orientation analysis method according to this embodiment will be described with reference to Fig. 6. Fig. 6 is a flowchart showing the resin flow direction analysis method according to this embodiment.

[0058] First, a tomographic image of the ferrule 10 is obtained (step S201). The tomographic image of the ferrule 10 can be obtained by, for example, a method using an X-ray CT apparatus or a method of observing a polished cross section of the ferrule 10 with a microscope.

[0059] Next, the orientation of the resin in the ferrule 10 is analyzed based on the tracer appearing in the tomographic image of the ferrule 10 (step S202). The flow direction of the resin may be determined from a tomographic image obtained from a single ferrule 10, or from tomographic images obtained from multiple ferrules 10. The orientation analysis may be performed visually using a microscope, or may be automatically performed by an image processing device. The analysis results are recorded in the image processing unit 123 of the analysis device 100, and may be used for quality control of multiple ferrules 10, etc.

[0060] [Effects] As described above, according to the present embodiment, by using at least one of the aggregate and the resin composition as a tracer, it is possible to estimate the orientation of the resin while suppressing anisotropy. Hereinafter, the effects of the present embodiment will be described in detail in comparison with the conventional technology.

[0061] For high-precision injection molded products that require dimensional accuracy on the submicron order, such as MT ferrules, it is desirable for the thermal dimensional changes caused by molding shrinkage and linear expansion coefficient to be isotropic. However, thermoplastic resins, especially crystalline resins, exhibit different dimensional changes in the flow direction (MD) and the perpendicular direction (TD) during molding, and are therefore anisotropic.

[0062] In addition, fibrous or needle-shaped inorganic particles are added as a filler or reinforcing material. The linear expansion coefficient of fibrous or needle-shaped inorganic particles is small. However, since the surrounding resin is restrained by the inorganic particles, the orientation of the resin composition around the inorganic particles differs in the length direction and the perpendicular direction, and the anisotropy of the dimensional change of the resin increases. That is, the fibrous or needle-shaped inorganic particles cannot expand and contract in the length direction, and the dimensional change is concentrated in the vertical direction. For this reason, it is preferable that the filler has a shape with little anisotropy, such as a spherical shape, a polygonal shape, an indefinite shape, or a crushed shape.

[0063] In this way, the anisotropy caused by the filler or reinforcing material can be reduced by selecting the shape of the inorganic particles, but the anisotropy of the thermoplastic resin itself is tolerated when used.

[0064] When molded products such as ferrules are mass-produced, even if they are manufactured using the same mold and under the same conditions, the dimensions of the molded products may differ depending on the production lot, resulting in defective products. In this case, the cause of the defective products must be investigated from among many manufacturing conditions such as materials, molds, and molding machines in the manufacturing process, and measures must be taken. Such cause investigation and measures require a lot of time and effort, which may result in a decrease in productivity. In addition, since the cause investigation relies heavily on the experienced intuition of the person in charge, the burden tends to be concentrated on certain experienced persons. For these reasons, the establishment of an analysis method based on objective information was desired.

[0065] Here, the inventors have found through intensive research that in many cases the cause is either mold variation or resin flow variation. Specifically, mold variation can be a slight shift of mold parts during manufacturing, or a slight change in the mold shape caused by wear of the mold by the resin. The dimensions of the molded product are also changed by such a mold. Resin flow variation is caused by changes in resin flow due to differences in resin viscosity depending on the material lot. That is, as described above, the orientation of the polymer, which has anisotropy in dimensional change, changes, and the direction of large molding shrinkage changes, which can cause the dimensions of the molded product to change. Therefore, if the orientation of the resin can be objectively evaluated, it is possible to identify one of the two causes described above, and the time and effort required for cause investigation can be greatly reduced.

[0066] As a technique for estimating the orientation, it may be possible to use a tracer added to a filler. The technique described in the above-mentioned Patent Document 1 uses fibrous inorganic particles as a tracer to estimate the orientation of the resin from the fiber direction. However, since the fibrous inorganic particles cannot deform in accordance with the expansion and contraction of the surrounding resin, they restrain the deformation of the resin and increase the anisotropy of the injection molded product. In addition, JP-A-5-345328 describes a filler with small anisotropy. However, since the filler described in the same document has high symmetry, it is difficult to obtain information on the resin orientation from the filler. Furthermore, JP-A-2004-29415 describes a small amount of needle-shaped filler. However, even if the amount of needle-shaped filler is small, sufficient dimensional accuracy cannot be obtained in products that require dimensional accuracy at the submicron level.

[0067] There are also methods for directly analyzing molecular orientation without using tracers, but the equipment is generally expensive and requires highly specialized skills for sample preparation, operation, analysis, etc. In addition, since the measurement and analysis take time, it is not realistic to adopt such analysis methods at manufacturing sites.

[0068] In view of the above, it has been desired to estimate the resin orientation in a molded product in a short time at the manufacturing site using a simple method without impairing the isotropy of the molded product. Through intensive research, the inventors have discovered that the following characteristic configuration makes it possible to estimate the resin orientation without impairing the isotropy of the resin.

[0069] First, the tracer is preferably anisotropic. For example, the tracer in this embodiment has a predetermined aspect ratio, such as flat, rod, or needle shape. By observing the longitudinal direction of the tracer with a microscope, X-ray CT device, or the like, it is possible to estimate the flow direction of the resin.

[0070] Secondly, it is preferable that the tracer has flexibility. As described above, the tracer in this embodiment is composed of an aggregate of small-diameter inorganic particles or a resin composition. This allows the tracer to deform in response to the expansion and contraction of the resin, minimizing the effect on the dimensional accuracy and anisotropy of the resin. The aggregate of inorganic particles has high flexibility compared to a single inorganic particle.

[0071] Thirdly, the filler preferably has isotropy or symmetry in shape. In this embodiment, non-fibrous inorganic particles having isotropy are added as the filler. This makes it possible to suppress the increase in anisotropy of the resin caused by the filler.

[0072] Fourth, it is preferable that the filler is distinguishable from the tracer. In this embodiment, the filler is composed of non-fibrous inorganic particles and has small anisotropy. Therefore, it is possible to distinguish the tracer having anisotropy from the filler.

[0073] According to the above-mentioned characteristic configuration, it was confirmed by the following examples that it is possible to estimate the orientation of the resin while suppressing anisotropy.

[0074] [Example] Next, examples of the present invention and comparative examples will be described. Injection molding resin compositions for use in MT ferrules were produced while changing the production conditions. [Table 1]

[0075] Table 1 shows evaluations 1 and 2 of the first thermoplastic resin (parts by weight), non-fibrous inorganic particles (parts by weight), non-fibrous inorganic particles (% by weight), aggregates (parts by weight), resin composition (parts by weight), heterogeneous portion (tracer), and evaluation 3 of anisotropy caused by the tracer. "Evaluation 1" indicates whether or not a tracer that satisfies the criteria (aspect ratio is 2 to 20 and major axis is 25 μm to 100 μm) can be confirmed by microscope observation. If a tracer that satisfies the criteria can be confirmed, Evaluation 1 is judged as good (OK), and if it cannot be confirmed, Evaluation 1 is judged as bad (NG). "Evaluation 2" indicates whether or not a tracer that satisfies the criteria (aspect ratio is 2 to 20 and major axis is 25 μm to 100 μm) can be confirmed by X-ray CT observation. If a tracer that satisfies the criteria can be confirmed, Evaluation 1 is judged as good (OK), and if it cannot be confirmed, Evaluation 1 is judged as bad (NG). "Rating 3" indicates whether the effects of anisotropy and dimensional change caused by the tracer can be confirmed. If the effects of anisotropy and dimensional change caused by the tracer cannot be confirmed, then Rating 3 is judged as good (OK), and if they can be confirmed, then Rating 3 is judged as poor (NG).

[0076] [Example 1] In Example 1, the following materials were prepared as each component of the resin composition for injection molding. As the first thermoplastic resin, 100 parts by weight of crosslinked polyphenylene sulfide resin (manufactured by DIC Corporation, melt viscosity 27 Pa·s (equivalent to JIS K-7210, measurement temperature 300°C, load 20 kgf, die 1.0 mm×10 mm)) was prepared. As the non-fibrous inorganic particles as a filler, 300 parts by weight of high-purity spherical silica filler (particle size 25 μm or less, manufactured by Admatechs Co., Ltd.) was added. As the material of the resin composition for injection molding, 74.6% by weight of non-fibrous inorganic particles was added. As the pigment for coloring, 2 parts by weight of Toka Black #7360SB (trade name, manufactured by Tokai Carbon Co., Ltd.), which is a carbon black for coloring, was added. As the aggregate of the second inorganic particles for the tracer, 0.1 parts by weight of Toka Black #7360SB (trade name, manufactured by Tokai Carbon Co., Ltd.), which is a carbon black, was added. No second thermoplastic resin or resin composition for the tracer was added.

[0077] After mixing the above materials, the mixture was kneaded in a twin-screw extruder at 350°C and a screw rotation speed of 400 rpm to produce pellets. The pellets were hot pressed and then polished, and the flat resin composition was exposed on the pellet surface. The exposed resin composition had a lower brightness than the first thermoplastic resin portion, so it could be identified using a microscope. Furthermore, this resin composition had a common peak with the first thermoplastic resin by qualitative analysis using FT-IR. Therefore, it was confirmed that the main component of the resin composition was the first thermoplastic resin.

[0078] Next, an MT ferrule was molded using the resin product for injection molding of Example 1. First, a cross-sectional observation of the MT ferrule was performed using a microscope and an X-ray CT scan, and tracers with an aspect ratio of 2 to 20 and a major axis of 25 μm to 100 μm were confirmed inside (Evaluation 1: OK, Evaluation 2: OK). In addition, no anisotropy or dimensional change due to the tracer was confirmed (Evaluation 3: OK).

[0079] [Example 2] In Example 2, 100 parts by weight of a crosslinked polyphenylene sulfide resin (manufactured by DIC Corporation, melt viscosity 27 Pa·s (equivalent to JIS K-7210, measurement temperature 300°C, load 20 kgf, die 1.0 mm×10 mm)) was prepared as the first thermoplastic resin. 300 parts by weight of high-purity spherical silica filler (particle size 25 μm or less, manufactured by Admatechs Co., Ltd.) was added as non-fibrous inorganic particles as a filler. As a material for the resin composition for injection molding, 74.6% by weight of non-fibrous inorganic particles was added. As a pigment for coloring, 2 parts by weight of Toka Black #7360SB (trade name, manufactured by Tokai Carbon Co., Ltd.), which is a carbon black for coloring, was added. No aggregates of second inorganic particles for the tracer were added. As the second thermoplastic resin for the tracer, the same type of PPS resin as the first thermoplastic resin was heated in oxygen at 320°C for 1 hour to turn black. The blackened PPS resin was pulverized and then sieved to obtain a resin composition with a major axis of 100 μm or less. 0.1 parts by weight of this resin composition was added in the kneading step.

[0080] After mixing the above materials except for the resin composition, the mixture was kneaded in a twin-screw extruder at 300°C and a screw speed of 400 rpm to produce pellets. The pellets were hot pressed and then polished, and the flat resin composition was not exposed on the pellet surface. Therefore, it was confirmed that the resin composition was not generated during the kneading process in Example 2.

[0081] Next, an MT ferrule was molded using the resin product for injection molding of Example 2. First, a cross-sectional observation of the MT ferrule was performed using X-ray CT, and a tracer with an aspect ratio of 2 to 20 and a major axis of 25 μm to 100 μm was confirmed inside (Evaluation 1: OK, Evaluation 2: OK). In addition, no anisotropy or dimensional change due to the tracer was confirmed (Evaluation 3: OK).

[0082] [Example 3] In Example 3, 100 parts by weight of a crosslinked polyphenylene sulfide resin (manufactured by DIC Corporation, melt viscosity 27 Pa·s (equivalent to JIS K-7210, measurement temperature 300°C, load 20 kgf, die 1.0 mm×10 mm)) was prepared as the first thermoplastic resin. 300 parts by weight of high-purity spherical silica filler (particle size 25 μm or less, manufactured by Admatechs Co., Ltd.) was added as non-fibrous inorganic particles as a filler. As a material for the resin composition for injection molding, 74.6% by weight of non-fibrous inorganic particles was added. As a pigment for coloring, 2 parts by weight of Toka Black #7360SB (trade name, manufactured by Tokai Carbon Co., Ltd.), which is a carbon black for coloring, was added. As an aggregate of second inorganic particles for the tracer, 0.1 parts by weight of Toka Black #7360SB (trade name, manufactured by Tokai Carbon Co., Ltd.), which is a carbon black, was added. The second thermoplastic resin and resin composition for the tracer were not added.

[0083] After mixing the above materials, the mixture was kneaded in a twin-screw extruder at 300°C and a screw rotation speed of 400 rpm to produce pellets. The pellets were hot pressed and then polished, and the flat resin composition was not exposed on the pellet surface. Therefore, it was confirmed that no resin composition was produced during the kneading process in Example 3.

[0084] Next, an MT ferrule was molded using the resin product for injection molding of Example 3. First, a cross-sectional observation of the MT ferrule was performed using X-ray CT, and tracers with an aspect ratio of 2 to 20 and a major axis of 25 μm to 100 μm were confirmed inside (Evaluation 1: OK, Evaluation 2: OK). In addition, no anisotropy or dimensional change due to the tracer was confirmed (Evaluation 3: OK).

[0085] [Example 4] In Example 4, 100 parts by weight of a crosslinked polyphenylene sulfide resin (manufactured by DIC Corporation, melt viscosity 27 Pa·s (equivalent to JIS K-7210, measurement temperature 300°C, load 20 kgf, die 1.0 mm×10 mm)) was prepared as the first thermoplastic resin. 300 parts by weight of high-purity spherical silica filler (particle size 25 μm or less, manufactured by Admatechs Co., Ltd.) was added as non-fibrous inorganic particles as a filler. As a material for the resin composition for injection molding, 74.9% by weight of non-fibrous inorganic particles was added. 0.5 parts by weight of Toka Black #7360SB (trade name, manufactured by Tokai Carbon Co., Ltd.), which is a coloring carbon black, was added as a coloring pigment. 0.1 parts by weight of silica particles (particle size 1 μm or less, manufactured by Admatechs Co., Ltd.) was added as an aggregate of second inorganic particles for a tracer. In order to suppress the dispersion of the silica particles in the first thermoplastic resin, no surface treatment agent or the like was used on the silica particles. No second thermoplastic resin or resin composition for the tracer was added.

[0086] After mixing the above materials, the mixture was kneaded in a twin-screw extruder at 350°C and a screw rotation speed of 400 rpm to produce pellets. The pellets were hot pressed and then polished, and the flat resin composition was exposed on the pellet surface. The exposed resin composition had a lower brightness than the first thermoplastic resin portion, so it could be identified using a microscope. Furthermore, this resin composition had a common peak with the first thermoplastic resin by qualitative analysis using FT-IR. Therefore, it was confirmed that the main component of the resin composition was the first thermoplastic resin.

[0087] Next, an MT ferrule was molded using the resin product for injection molding of Example 4. First, a cross-sectional observation of the MT ferrule was performed using X-ray CT, and tracers with an aspect ratio of 2 to 20 and a major axis of 25 μm to 100 μm were confirmed inside (Evaluation 1: OK, Evaluation 2: OK). In addition, no anisotropy or dimensional change due to the tracer was confirmed (Evaluation 3: OK).

[0088] [Example 5] In Example 5, the following materials were prepared as each component of the resin composition for injection molding. As the first thermoplastic resin, 100 parts by weight of crosslinked polyphenylene sulfide resin (manufactured by DIC Corporation, melt viscosity 27 Pa·s (equivalent to JIS K-7210, measurement temperature 300°C, load 20 kgf, die 1.0 mm×10 mm)) was prepared. As the non-fibrous inorganic particles as a filler, 200 parts by weight of high-purity spherical silica filler (particle size 25 μm or less, manufactured by Admatechs Co., Ltd.) was added. As the material of the resin composition for injection molding, 66.2% by weight of non-fibrous inorganic particles was added. As the pigment for coloring, 2 parts by weight of Toka Black #7360SB (trade name, manufactured by Tokai Carbon Co., Ltd.), which is a carbon black for coloring, was added. As the aggregate of the second inorganic particles for the tracer, 0.1 parts by weight of Toka Black #7360SB (trade name, manufactured by Tokai Carbon Co., Ltd.), which is a carbon black, was added. No second thermoplastic resin or resin composition for the tracer was added.

[0089] After mixing the above materials, the mixture was kneaded in a twin-screw extruder at 350°C and a screw rotation speed of 400 rpm to produce pellets. The pellets were hot pressed and then polished, and the flat resin composition was exposed on the pellet surface. The exposed resin composition had a lower brightness than the first thermoplastic resin portion, so it could be identified using a microscope. Furthermore, this resin composition had a common peak with the first thermoplastic resin by qualitative analysis using FT-IR. Therefore, it was confirmed that the main component of the resin composition was the first thermoplastic resin.

[0090] Next, an MT ferrule was molded using the resin product for injection molding of Example 5. First, a cross-sectional observation of the MT ferrule was performed using a microscope and an X-ray CT scan, and a tracer with an aspect ratio of 2 to 20 and a major axis of 25 μm to 100 μm was confirmed inside (Evaluation 1: OK, Evaluation 2: OK). In addition, no anisotropy or dimensional change due to the tracer was confirmed (Evaluation 3: OK).

[0091] [Example 6] In Example 6, the following materials were prepared as each component of the resin composition for injection molding. As the first thermoplastic resin, 100 parts by weight of crosslinked polyphenylene sulfide resin (manufactured by DIC Corporation, melt viscosity 27 Pa·s (equivalent to JIS K-7210, measurement temperature 300°C, load 20 kgf, die 1.0 mm×10 mm)) was prepared. As the non-fibrous inorganic particles as a filler, 300 parts by weight of high-purity spherical silica filler (particle size 25 μm or less, manufactured by Admatechs Co., Ltd.) was added. As the material of the resin composition for injection molding, 74.6% by weight of non-fibrous inorganic particles was added. As the pigment for coloring, 2 parts by weight of Toka Black #7360SB (trade name, manufactured by Tokai Carbon Co., Ltd.), which is a carbon black for coloring, was added. As the aggregate of the second inorganic particles for the tracer, 0.05 parts by weight of Toka Black #7360SB (trade name, manufactured by Tokai Carbon Co., Ltd.), which is a carbon black, was added. No second thermoplastic resin or resin composition for the tracer was added.

[0092] After mixing the above materials, the mixture was kneaded in a twin-screw extruder at 350°C and a screw rotation speed of 400 rpm to produce pellets. The pellets were hot pressed and then polished, and the flat resin composition was exposed on the pellet surface. The exposed resin composition had a lower brightness than the first thermoplastic resin portion, so it could be identified using a microscope. Furthermore, this resin composition had a common peak with the first thermoplastic resin by qualitative analysis using FT-IR. Therefore, it was confirmed that the main component of the resin composition was the first thermoplastic resin.

[0093] Next, an MT ferrule was molded using the resin product for injection molding of Example 6. First, a cross-sectional observation of the MT ferrule was performed using a microscope and an X-ray CT scan, and a tracer with an aspect ratio of 2 to 20 and a major axis of 25 μm to 100 μm was confirmed inside (Evaluation 1: OK, Evaluation 2: OK). In addition, no anisotropy or dimensional change due to the tracer was confirmed (Evaluation 3: OK).

[0094] [Example 7] In Example 7, the following materials were prepared as each component of the resin composition for injection molding. As the first thermoplastic resin, 100 parts by weight of crosslinked polyphenylene sulfide resin (manufactured by DIC Corporation, melt viscosity 27 Pa·s (equivalent to JIS K-7210, measurement temperature 300°C, load 20 kgf, die 1.0 mm×10 mm)) was prepared. As the non-fibrous inorganic particles as a filler, 300 parts by weight of high-purity spherical silica filler (particle size 25 μm or less, manufactured by Admatechs Co., Ltd.) was added. As the material of the resin composition for injection molding, 74.4% by weight of non-fibrous inorganic particles was added. As the pigment for coloring, 2 parts by weight of Toka Black #7360SB (trade name, manufactured by Tokai Carbon Co., Ltd.), which is a carbon black for coloring, was added. As the aggregate of the second inorganic particles for the tracer, 1 part by weight of Toka Black #7360SB (trade name, manufactured by Tokai Carbon Co., Ltd.), which is a carbon black, was added. No second thermoplastic resin or resin composition for the tracer was added.

[0095] After mixing the above materials, the mixture was kneaded in a twin-screw extruder at 350°C and a screw rotation speed of 400 rpm to produce pellets. The pellets were hot pressed and then polished, and the flat resin composition was exposed on the pellet surface. The exposed resin composition had a lower brightness than the first thermoplastic resin portion, so it could be identified using a microscope. Furthermore, this resin composition had a common peak with the first thermoplastic resin by qualitative analysis using FT-IR. Therefore, it was confirmed that the main component of the resin composition was the first thermoplastic resin.

[0096] Next, an MT ferrule was molded using the resin product for injection molding of Example 7. First, a cross-sectional observation of the MT ferrule was performed using a microscope and an X-ray CT scan, and a tracer with an aspect ratio of 2 to 20 and a major axis of 25 μm to 100 μm was confirmed inside (Evaluation 1: OK, Evaluation 2: OK). In addition, no anisotropy or dimensional change due to the tracer was confirmed (Evaluation 3: OK).

[0097] [Example 8] In Example 8, the following materials were prepared as each component of the resin composition for injection molding. As the first thermoplastic resin, 100 parts by weight of crosslinked polyphenylene sulfide resin (manufactured by DIC Corporation, melt viscosity 27 Pa·s (equivalent to JIS K-7210, measurement temperature 300°C, load 20 kgf, die 1.0 mm×10 mm)) was prepared. As the non-fibrous inorganic particles as a filler, 300 parts by weight of high-purity spherical silica filler (particle size 25 μm or less, manufactured by Admatechs Co., Ltd.) was added. As the material of the resin composition for injection molding, 74.6% by weight of non-fibrous inorganic particles was added. As the pigment for coloring, 2 parts by weight of Asahi Carbon SB320, which is carbon black for coloring, was added. As the aggregate of the second inorganic particles for the tracer, 0.1 parts by weight of Asahi Carbon SB320, which is carbon black, was added. The second thermoplastic resin and resin composition for the tracer were not added.

[0098] After mixing the above materials, the mixture was kneaded in a twin-screw extruder at 350°C and a screw rotation speed of 400 rpm to produce pellets. The pellets were hot pressed and then polished, and the flat resin composition was exposed on the pellet surface. The exposed resin composition had a lower brightness than the first thermoplastic resin portion, so it could be identified using a microscope. Furthermore, this resin composition had a common peak with the first thermoplastic resin by qualitative analysis using FT-IR. Therefore, it was confirmed that the main component of the resin composition was the first thermoplastic resin.

[0099] Next, an MT ferrule was molded using the resin product for injection molding of Example 8. First, a cross-sectional observation of the MT ferrule was performed using a microscope and an X-ray CT scan, and a tracer with an aspect ratio of 2 to 20 and a major axis of 25 μm to 100 μm was confirmed inside (Evaluation 1: OK, Evaluation 2: OK). In addition, no anisotropy or dimensional change due to the tracer was confirmed (Evaluation 3: OK).

[0100] [Example 9] In Example 9, the following materials were prepared as each component of the resin composition for injection molding. As the first thermoplastic resin, 100 parts by weight of crosslinked polyphenylene sulfide resin (manufactured by DIC Corporation, melt viscosity 27 Pa·s (equivalent to JIS K-7210, measurement temperature 300°C, load 20 kgf, die 1.0 mm×10 mm)) was prepared. As the non-fibrous inorganic particles as the filler, 300 parts by weight of a mixture of high-purity spherical silica filler (particle size 25 μm or less, manufactured by Admatechs Co., Ltd.) and amorphous silica filler (particle size 25 μm or less, manufactured by Tatsumori Co., Ltd.) was added. As the material of the resin composition for injection molding, 74.6% by weight of non-fibrous inorganic particles was added. As the pigment for coloring, 2 parts by weight of Asahi Carbon SB320, which is carbon black for coloring, was added. As the aggregate of the second inorganic particles for the tracer, 0.1 parts by weight of Asahi Carbon SB320, which is carbon black, was added. No second thermoplastic resin or resin composition for the tracer was added.

[0101] After mixing the above materials, the mixture was kneaded in a twin-screw extruder at 350°C and a screw rotation speed of 400 rpm to produce pellets. The pellets were hot pressed and then polished, and the flat resin composition was exposed on the pellet surface. The exposed resin composition had a lower brightness than the first thermoplastic resin portion, so it could be identified using a microscope. Furthermore, this resin composition had a common peak with the first thermoplastic resin by qualitative analysis using FT-IR. Therefore, it was confirmed that the main component of the resin composition was the first thermoplastic resin.

[0102] Next, an MT ferrule was molded using the resin product for injection molding of Example 9. First, a cross-sectional observation of the MT ferrule was performed using a microscope and an X-ray CT scan, and a tracer with an aspect ratio of 2 to 20 and a major axis of 25 μm to 100 μm was confirmed inside (Evaluation 1: OK, Evaluation 2: OK). In addition, no anisotropy or dimensional change due to the tracer was confirmed (Evaluation 3: OK).

[0103] [Comparative Example 1] In Comparative Example 1, 100 parts by weight of a crosslinked polyphenylene sulfide resin (manufactured by DIC Corporation, melt viscosity 27 Pa·s (equivalent to JIS K-7210, measurement temperature 300°C, load 20 kgf, die 1.0 mm×10 mm)) was prepared as the first thermoplastic resin. 300 parts by weight of high-purity spherical silica filler (particle size 25 μm or less, manufactured by Admatechs Co., Ltd.) was added as non-fibrous inorganic particles serving as a filler. As a material for the resin composition for injection molding, 75.0% by weight of non-fibrous inorganic particles was added. No pigment was added for coloring. No aggregates of second inorganic particles were added as a tracer. No second thermoplastic resin and resin composition for tracers were added.

[0104] After mixing the above materials, the mixture was kneaded in a twin-screw extruder at 300°C and a screw rotation speed of 400 rpm to produce pellets. The pellets were hot pressed and then polished, and the flat resin composition was not exposed on the pellet surface. Therefore, it was confirmed that no resin composition was produced during the kneading process in Comparative Example 1.

[0105] Next, an MT ferrule was molded using the resin product for injection molding of Comparative Example 1. First, a cross-sectional observation of the MT ferrule was performed using X-ray CT, and no tracer with an aspect ratio of 2 to 20 and a major axis of 25 μm to 100 μm was confirmed inside (Evaluation 1: NG, Evaluation 2: NG). In addition, no anisotropy or dimensional change caused by the tracer was confirmed (Evaluation 3: OK).

[0106] [Comparative Example 2] In Comparative Example 2, 100 parts by weight of a crosslinked polyphenylene sulfide resin (manufactured by DIC Corporation, melt viscosity 27 Pa·s (equivalent to JIS K-7210, measurement temperature 300°C, load 20 kgf, die 1.0 mm x 10 mm)) was prepared as the first thermoplastic resin. 300 parts by weight of high-purity spherical silica filler (particle size 25 μm or less, manufactured by Admatechs Co., Ltd.) was added as non-fibrous inorganic particles as a filler. As a material for a resin composition for injection molding, 75.0% by weight of non-fibrous inorganic particles was added. No pigment was added for coloring. No aggregates of second inorganic particles were added as a tracer. As a second thermoplastic resin for a tracer, a PPS resin of the same type as the first thermoplastic resin was heated in oxygen at 320°C for 1 hour to turn black. The blackened PPS resin was crushed and then sieved to obtain a resin composition with a major axis of 25 μm or less. This resin composition was added in an amount of 0.1 part by weight during the kneading step.

[0107] After mixing the above materials except for the resin composition, the mixture was kneaded in a twin-screw extruder at 300°C and a screw speed of 400 rpm to produce pellets. The pellets were hot pressed and then polished, and the flat resin composition was not exposed on the pellet surface. Therefore, it was confirmed that the resin composition was not produced during the kneading process in Comparative Example 2.

[0108] Next, an MT ferrule was molded using the resin product for injection molding of Comparative Example 2. First, a cross-sectional observation of the MT ferrule was performed using X-ray CT, and no tracer with an aspect ratio of 2 to 20 and a major axis of 25 μm to 100 μm was confirmed inside (Evaluation 1: NG, Evaluation 2: NG). In addition, no anisotropy or dimensional change caused by the tracer was confirmed (Evaluation 3: OK).

[0109] As described above, according to this embodiment, by using the aggregate and the resin composition as a tracer, it is possible to estimate the orientation of the resin while suppressing anisotropy.

[0110] The present invention is not limited to the above-mentioned embodiment, and various modifications are possible. In addition, for the parts not specifically described or illustrated in the embodiment, well-known and publicly known techniques in the technical field can be appropriately applied. The resin molded product manufactured from the above-mentioned resin composition for injection molding is not limited to parts for optical electronic devices such as ferrules, and can be applied to various parts and products. [Explanation of symbols]

[0111] 10…Ferrule 12...Optical fiber insertion hole 14...Optical fiber core 16...Optical fiber 18...End face 20...Guide pin insertion hole 22…Guide pin

Claims

1. A resin composition for injection molding comprising a first thermoplastic resin and a filler comprising non-fibrous first inorganic particles, Further comprising at least one of an aggregate of second inorganic particles or a resin composition of a second thermoplastic resin; In the lengths of the aggregate and the resin composition in three mutually perpendicular directions, a ratio of a longest first length to a shortest second length is 2 or more and 20 or less, and the first length is 25 μm or more and 100 μm or less, the first inorganic particles having a particle diameter of 25 μm or more are not contained inside the aggregate or the resin composition, 1. A resin composition for injection molding, wherein the first thermoplastic resin and the second thermoplastic resin are the same type of resin.

2. The cumulative 99% particle diameter D of the first inorganic particles 99 2. The resin composition for injection molding according to claim 1, wherein the particle size is 25 μm or less.

3. 2. The resin composition for injection molding according to claim 1, wherein the second inorganic particles have a particle size of 1 μm or less.

4. 2. The resin composition for injection molding according to claim 1, wherein the softening temperature of the resin composition is higher than the softening temperature of the first thermoplastic resin.

5. 2. The resin composition for injection molding according to claim 1, wherein the amount of the first inorganic particles added is 50% by weight or more and 85% by weight or less.

6. 2. The injection molding resin composition of claim 1, wherein the first thermoplastic resin, the aggregate, and the resin composition are black in color.

7. 2. The resin composition for injection molding according to claim 1, wherein the first thermoplastic resin is a polyarylene sulfide.

8. 2. The resin composition for injection molding according to claim 1, wherein the first inorganic particles are spherical or polygonal silica particles.

9. 2. The resin composition for injection molding according to claim 1, wherein the second inorganic particles are carbon black.

10. 2. The resin composition for injection molding according to claim 1, wherein the aggregate and the resin composition are used as a tracer for determining anisotropy of an injection molded article.

11. An injection molded article comprising the resin composition for injection molding according to any one of claims 1 to 10.

12. A part for optoelectronic devices comprising the resin composition for injection molding according to any one of claims 1 to 10.

13. A ferrule for connecting optical fibers, comprising the resin composition for injection molding according to claim 1 .

14. A first step of kneading a first thermoplastic resin, non-fibrous first inorganic particles, and at least one of an aggregate of second inorganic particles and a resin composition of a second thermoplastic resin; a second step of injection molding the mixture from the first step; In the lengths of the aggregate and the resin composition in three mutually perpendicular directions, a ratio of a longest first length to a shortest second length is 2 or more and 20 or less, and the first length is 25 μm or more and 100 μm or less, the first inorganic particles having a particle diameter of 25 μm or more are not contained inside the aggregate or the resin composition, A method for manufacturing an injection molded product, wherein the first thermoplastic resin and the second thermoplastic resin are the same type of resin.

15. The cumulative 99% particle diameter D of the first inorganic particles 99 The method for producing an injection molded product according to claim 14, characterized in that the thickness of the molded article is 25 μm or less.

16. The method for producing an injection molded product according to claim 14, wherein the particle diameter of the second inorganic particles is 1 μm or less.

17. 15. The method for producing an injection molded product according to claim 14, wherein in the first step, the resin composition is formed by blackening a part of the first thermoplastic resin.

18. acquiring a tomographic image of an injection-molded article including a first thermoplastic resin, non-fibrous first inorganic particles, and at least one of an aggregate of second inorganic particles and a resin composition of the second thermoplastic resin; determining an orientation of the aggregate or the resin composition in the tomographic image; In the lengths of the aggregate and the resin composition in three mutually perpendicular directions, a ratio of a longest first length to a shortest second length is 2 or more and 20 or less, and the first length is 25 μm or more and 100 μm or less, A method for analyzing an injection-molded product, characterized in that the first inorganic particles having a particle size of 25 μm or more are not contained inside the aggregate or the resin composition.

19. The cumulative 99% particle diameter D of the first inorganic particles 99 The method for analyzing an injection molded product according to claim 18, wherein the thickness is 25 μm or less.

20. 20. The method for analyzing an injection molded product according to claim 18, wherein the particle diameter of the second inorganic particles is 1 μm or less.

Citation Information

Patent Citations

  • Hot warpage analysis method for a liquid crystal polymer injection-molded article

    JP2014100879A

  • Components produced by thermoplastic processing of polymer / boron nitride compounds, polymer / boron nitride compounds for producing such components, methods for producing such components and uses thereof

    JP2016533282A